Healthcare Management Education - Forms and Contents - Szabados, György Norbert; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Felföldi, János; Szabados, Krisztián; Molnár, Anikó; Ráthonyi, Gergely (International Journal of Engineering and Management Sciences, 2022)
Gaining autonomy of a subfield of a private discipline has become plural up to the XXI. century. The appearance of the management discipline at the beginning of the XX. century mostly dealt with the industrial sector, and it was in relationship with the maximalization of efficiency. For now management became on his own in the healthcare sector, certainly regarding the education forms, which is emphasized the numerous educational ways on international level. Educational forms have a binary feature on national level, offering one BA and one MA possibility to learn. The objective of this study is to reveal diversity of the international education forms, illustrating their more important specifications, comparing them with the domestic relationship, all of which may highlight the need for new or novel education forms.